Demography, life-history trade-offs, and the gastrointestinal virome of wild chimpanzees. (9th November 2020) - Negrey, Jacob D.; Thompson, Melissa Emery; Langergraber, Kevin E.; Machanda, Zarin P.; Mitani, John C.; Muller, Martin N.; Otali, Emily; Owens, Leah A.; Wrangham, Richard W.; Goldberg, Tony L.
Abstract : In humans, senescence increases susceptibility to viral infection. However, comparative data on viral infection in free-living non-human primates—even in our closest living relatives, chimpanzees and bonobos ( Pan troglodytes and P. paniscus )—are relatively scarce, thereby constraining an evolutionary understanding of age-related patterns of viral infection. We investigated a population of wild eastern chimpanzees ( P. t. schweinfurthii ), using metagenomics to characterize viromes (full viral communities) in the faeces of 42 sexually mature chimpanzees (22 males, 20 females) from the Kanyawara and Ngogo communities of Kibale National Park, Uganda. We identified 12 viruses from at least four viral families possessing genomes of both single-stranded RNA and single-stranded DNA. Faecal viromes of both sexes varied with chimpanzee age, but viral richness increased with age only in males. This effect was largely due to three viruses, salivirus, porprismacovirus and chimpanzee stool-associated RNA virus (chisavirus), which occurred most frequently in samples from older males. This finding is consistent with the hypothesis that selection on males for early-life reproduction compromises investment in somatic maintenance, which has delayed consequences for health later in life, in this case reflected in viral infection and/or shedding. Faecal viromes are therefore useful for studying processes related to the divergent reproductive strategies of males and females, ageing, and sex differences in longevity. This article is part of the theme issue 'Evolution of the primate ageing process'.